RELATIONSHIP BETWEEN EMPLOYEES KNOWLEDGE AND ATTITUDES TOWARD GOOD MANUFACTURING PRACTICES FOR TRADITIONAL MEDICINES IN A SMALL-SCALE TRADITIONAL MEDICINE ENTERPRISE - Ni Luh Komang Ayu Widya Pratiwi; Dewa Ayu Manacika Diananda; Pande Komang Ayu Widhiani; Putu Diah Astika Veda; Putu Oka Samirana (Journal Pharmaceutical Science and Application, 2026)
Background: Small traditional medicine enterprises must implement Good Manufacturing Practice for Traditional Medicines (GMP-TM) to ensure that the resulting products meet established safety, quality, and efficacy requirements. The successful implementation of GMP-TM must be supported by the competence of the human resources involved. Adequate knowledge is expected to foster more good attitudes toward work standards or policies. However, research specifically examining this matter remains lacking. Objective: To determine the relationship between employees' knowledge and attitudes regarding GMP-TM at a small-scale traditional medicine enterprise. Methods: An analytical observational study using a cross-sectional design involving 30 participants (total sampling). The instrument used was a questionnaire, and data analysis was performed using Spearman's test. Results: All respondents had a good level of knowledge regarding the topic under study, namely 30 respondents (100%). A total of 28 respondents also demonstrated a very good attitude (93.33%), while 2 respondents (6.67%) had a good attitude. The Spearman correlation test yielded a p-value of 0.006 (p<0.05) and an r-value of 0.492. Conclusion: There is a significant relationship between the respondents' level of knowledge and attitudes, with a moderate strength of relationship and a positive direction.